Karakterisasi protease Bacillus sp. UGM5 - Titik Purwati Widowati; Soemitro Djojowidagdo; Setiyono Setiyono; Widya Asmara (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1999)
The objective of this experiment is to indentify the characters of proetease produced by Bacillus sp.UGM5.the protease secreted by Bacillus sp.UGM5 was first isolated,purified and then charactirezed.The crude enzyme has spesific actifity of 1.14 U/mg,however,the spesific activity of purified enzyme was increased by 23.8 times fold and recovery was 33.69%.The Page of nondenatured crude enzymes showes two type of proreases,however ,the SDS-Page of denatured purified enzyme showed four protein-bends with molecular weights of 55.5 kDa,18kDa respecetively.The optimum pH and temperature for the enzyme acrivity are 8.5 and 420C and belongs to serin protease type,with Km 3 X 10-3mM and Vmax 0.0890mM/30 minutes.The activity is not inhibited by Ca+2,Fe+2 and EDTA. INTISARITujuan penelitian ini adalah untuk mengkarakterisasi protease yang diproduksi Bacillus sp. UGM5. Protease yang disekresi oleh Bacillus sp.UGM5 pertama-tama diisolasi,dipurifikasi kemudian dikarakterisasi.Enzim kasar mempunyai spesifik 1,14 U/mg.Aktivitas spesifik enzim yang dimurnikan meningkat 23,8 kali dengan recovery 33,69%.Elektroforesis gel poliakrilamid enzim yang dipurifikasi dan didenaturisasi menunjukan ada empat pita protein dengan berat protein masing-masing 55,5 kDa,51 kDa,18 kDa,dan 15,5 kDa .ph dan temperatur optimum aktivitas enzim adalah 8,5 dan 420C,termasuk tipe protease serin,dengan nilai Km 3 X10-3mM dan Vmax 0,0890mM/30menit.Aktivitas enzim tidak dihambat oleh adanya ion Ca2+,Fe+3 dan EDTA.